Comparison of Personality Concepts According to Islam and the West - Mengki, Jias (International Journal of Education, Language, and Social Science, 2023)
Psychology is the science that studies human behavior and mental processes. This field includes the understanding of how humans think, feel, and behave. The method used in analysis and research in the field of literature studies involves critical review and evaluation of works of literature that are relevant to a particular topic or research question. Psychology studies various aspects of human life, including cognitive processes, emotions, motivations, perception, human development, social interaction, and mental disorders. Personality according to Islam is an integrated integration of the workings of aqliyah and nafsiyah based on Islamic beliefs that give birth to actions. Human personality is not formed and influenced by the shape of the body, face and other accessories. Human personality is formed by aqliyah and nafsiyah. Western approaches to personality can vary depending on the point of view used. However, in a general context, the Western approach to personality tends to be individualistic. The general goal in personality psychology is to understand and explain how individuals develop, maintain, and express their unique characteristics as individuals.